Sido Makmur Srandakan Bantul Livestock Farmer's Group Readiness to Utilize Fermented Feed to Increase Income - Kurniawati, Asih; Muhlisin, Muhlisin; Kusumastuti, Tri Anggraeni (Jurnal Sain Peternakan Indonesia, 2025)
The research aims to analyze the group's understanding and readiness in utilizing fermented feed preservation and income analysis, specifically focusing on the selection of a location within the Sido Makmur group in Srandakan District, Bantul Regency. The sample was selected as a convenience sample of as many as 17 out of 80 members who were willing to be interviewed. The research was conducted in a quantitative descriptive manner. Primary data was collected through direct interviews using a questionnaire tool. The primary data collected include respondent characteristics, land ownership, and readiness to utilize feed preservation. The results show that most farmers of productive age with formal education equivalent to high school have received training in feed preservation; their main occupation is farming. The forage potential comes from agricultural waste, plantations, grass, and legumes. Farmers are willing to provide fermented feed to livestock (82.50%) and interested in selling fermented feed (76.47%) in the form of drums with a capacity of 50 kg made by farmer’s group (47.06%), created by individual (70.59%) and plastic packaging (41.18%) Income from fermented feed in drum was IDR 37,970 and plastic was IDR 35,970. Selling price and product quality are essential factors in selling fermented feed. Fortunately, to support product quality, packaging and labelling support is needed.